Predictability and efficacy of therapeutic plasma exchange for hypertriglyceridemia induced acute pancreatitis. (April 2020) - Fei, Fei; Boshell, Nick; Williams, Lance A.
Abstract: Background: Hypertriglyceridemia induced acute pancreatitis is associated with more severe clinical course than acute pancreatitis caused by other etiologies. Therapeutic plasma exchange (TPE) is a potential treatment for patients with severe hypertriglyceridemia induced acute pancreatitis due to its rapid effect in lowering triglycerides (TG) levels and reducing inflammatory cytokines. However, clinical data regarding the effectiveness and safety of TPE is limited. Methods: We retrospectively reviewed eight cases of hypertriglyceridemia induced acute pancreatitis and treated with TPE. Patients' demographic data, personal history, clinical course, laboratory results, apheresis data and clinical outcome were collected and analyzed. Results: At initial presentation, the average TG levels for the eight patients was 3381.6 mg/dl (SD: 1491.6 mg/dl). Twelve procedures were performed on the eight patients in the study, and TG levels decreased by an average of 2673.2 mg/dl (SD: 2306.3 mg/dl) with a corresponding average reduction rate of 60.3 % (SD:21.1 %), ranging from 14.6%–84.9%. A 60 % or greater reduction was achieved in 66.7 % of all the procedures; however, the degree of reduction for each procedure was not predictable, even among repeat procedures on the same patient. Conclusions: Our study indicates that TPE is an effective and safe treatment option for patients with hypertriglyceridemia induced acute pancreatitis. However, due to the unpredictability of TG removal, repeat procedures may be necessary for some patients.